2004
DOI: 10.1073/pnas.0405271101
|View full text |Cite
|
Sign up to set email alerts
|

The regulated long-term delivery of therapeutic proteins by using antigen-specific B lymphocytes

Abstract: Memory lymphocytes are important mediators of the immune response. These cells are long-lived and undergo clonal expansion upon reexposure to specific antigen, differentiating into effector cells that secrete Ig or cytokines while maintaining a residual pool of memory T and B lymphocytes. Here, the ability of antigenspecific lymphocytes to undergo repeated cycles of antigen-driven clonal expansion and contraction is exploited in a therapeutic protocol aimed at regulating protein delivery. The principle of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 42 publications
(34 reference statements)
0
18
0
Order By: Relevance
“…The induction of Epo through HIF PHI has several potential advantages over rHuEpo, including ease of administration, lack of immunogenicity, [36][37][38] and the potential coordinate induction of other genes important for erythropoiesis. Several gene-transfer vector systems have also used Epo as a proof of principle for delivery of a therapeutic protein, [39][40][41][42][43] but these systems are cumbersome for clinical application. Recently, a nonspecific GATA inhibitor, K-11706, was shown to induce epo in Hep3B cells and elevate epo in mice after oral administration.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of Epo through HIF PHI has several potential advantages over rHuEpo, including ease of administration, lack of immunogenicity, [36][37][38] and the potential coordinate induction of other genes important for erythropoiesis. Several gene-transfer vector systems have also used Epo as a proof of principle for delivery of a therapeutic protein, [39][40][41][42][43] but these systems are cumbersome for clinical application. Recently, a nonspecific GATA inhibitor, K-11706, was shown to induce epo in Hep3B cells and elevate epo in mice after oral administration.…”
Section: Discussionmentioning
confidence: 99%
“…In our immuno‐regulated approach to gene therapy (Takacs et al , 2004), antigen‐specific lymphocytes genetically engineered to produce human epo (hepo) upon antigen challenge are transferred into anaemic mice. The subsequent administration of antigen to these mice can then be used to drive the activation and expansion of the transduced lymphocyte population, thereby increasing the production of hepo in the serum of the anaemic mice and restoring normal haematocrit values (Takacs et al , 2004). We recently demonstrated the feasibility of this system using hepo‐producing donor lymphocytes obtained from a convenient source (hepo‐transgenic mice) (Takacs et al , 2004).…”
mentioning
confidence: 99%
“…The subsequent administration of antigen to these mice can then be used to drive the activation and expansion of the transduced lymphocyte population, thereby increasing the production of hepo in the serum of the anaemic mice and restoring normal haematocrit values (Takacs et al , 2004). We recently demonstrated the feasibility of this system using hepo‐producing donor lymphocytes obtained from a convenient source (hepo‐transgenic mice) (Takacs et al , 2004). In the current study, we investigate the precise effects of hepo administration by this route on erythropoietic development in epo‐deficient mice.…”
mentioning
confidence: 99%
“…Not only would there need to be reassurance regarding the absence of oncogenicity, but it would also be imperative to show that tight control of the activity of the transferred gene can be achieved. This may be possible using a number of pharmacologic strategies or potentially by exposure to a rare antigen, when the transgene is expressed in a specific B cell clone (71). Interestingly, animal experiments have shown that linking the EPO transgene to a hypoxia-responsive DNA element (the HIF binding site) can establish an oxygen-dependent feedback regulation of the transgene, similar to that of the endogenous EPO gene (72).…”
Section: Epo Gene Therapymentioning
confidence: 99%